2013
DOI: 10.1186/1471-2407-13-502
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-encoded mitochondrial MTO1 and MRPL41 are regulated in an opposite epigenetic mode based on estrogen receptor status in breast cancer

Abstract: BackgroundMTO1 and MRPL41 are nuclear-encoded mitochondrial genes encoding a mitochondrial tRNA-modifying enzyme and a mitochondrial ribosomal protein, respectively. Although both genes have been known to have potential roles in cancer, little is known about their molecular regulatory mechanism, particularly from an epigenetic approach. In this study, we aimed to address their epigenetic regulation through the estrogen receptor (ER) in breast cancer.MethodsDigital differential display (DDD) was conducted to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…If the expression of MRPS23 was inhibited, it could disturb the mitochondrial protein synthesis, affect function of mitochondrial and impair breast cancer cell proliferation. Several studies indicate that the ribosomal proteins and MRPs may be directly involved in the process of cancer proliferation and metastasis [ 25 , 26 ], which are dependent on the stimulated activity of p53 and p21 WAF1/CIP1 [ 16 , 27 , 28 ]. Yoo et al reported that the MRPL41 suppresses cell growth in association with p53, p27 Kip1 [ 15 ] and p21 WAF1/CIP1 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the expression of MRPS23 was inhibited, it could disturb the mitochondrial protein synthesis, affect function of mitochondrial and impair breast cancer cell proliferation. Several studies indicate that the ribosomal proteins and MRPs may be directly involved in the process of cancer proliferation and metastasis [ 25 , 26 ], which are dependent on the stimulated activity of p53 and p21 WAF1/CIP1 [ 16 , 27 , 28 ]. Yoo et al reported that the MRPL41 suppresses cell growth in association with p53, p27 Kip1 [ 15 ] and p21 WAF1/CIP1 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have examined the biological functions and the possible mechanisms of mitochondrial ribosomal proteins (MRPs) in cancers individually. Several evidence have shown that MRPs are involved in cell proliferation and mitochondrial apoptosis through the p21 WAF1/CIP1 [ 13 ], p53 [ 14 16 ] and cytochrome c (Cyt c) -mediated pathway [ 17 ]. p21 WAF1/CIP1 may be regulated through either p53-dependent [ 18 ] or p53-independent mechanism [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study has shown that MTO1 mutations are associated with a mitochondrial disorder characterized by hypertrophic cardiomyopathy, lactic acidosis, and MRC deficiency [ 16 ]. Recently, the MTO1 gene was also reported to play a role in breast cancer tissues and cells [ 17 ]. This indicates that the function of the MTO1 gene may be more complicated than previously considered.…”
Section: Discussionmentioning
confidence: 99%
“…Second, mitochondrial ribosomal proteinencoding genes might be the anti-oncogenes to serve as new biomarkers and therapeutic targets. For example, bcl-2-interacting mitochondrial ribosomal protein L41 (MRPL41) is differentially expressed in carcinomas to associate with various epigenetic states [8]. Mitochondrial ribosomal protein S23 (MRPS23) is involved in cancer cell proliferation, which might serve as the therapeutic target [9].…”
Section: Introductionmentioning
confidence: 99%